Temporal trends in anti-vaccine discourse on Twitter. Issue 35 (14th August 2019) - Gunaratne, Keith; Coomes, Eric A.; Haghbayan, Hourmazd
Abstract: Despite vaccination's role in preventing communicable diseases, misinformation threatens uptake. Social media may disseminate such anti-vaccination messages. We characterized trends in pro- and anti-vaccination discourse on Twitter. All tweets between 2010 and 2019 containing vaccine-related hashtags were identified. Pro- and anti-vaccine tweets and users per quarter (3-months) were tabulated; discussion subcommunities were identified with network analysis. 1, 637, 712 vaccine-related tweets were identified from 154 pro-vaccine and 125 anti-vaccine hashtags, with 86% of users posting exclusively pro-vaccine and 12% posting exclusively anti-vaccine hashtags. Pro-vaccine tweet volumes are larger than anti-vaccine tweets and consistently increase over time. In contrast, anti-vaccine tweet volumes have decreased since 2014, despite an increasing anti-vaccine user-base. Users infrequently responded across pro/anti-vaccine alignment (0.2%). Despite greater volumes of pro-vaccination discourse in recent years, and the anti-vaccination content userbase being smaller, the anti-vaccine community continues to grow in size. This finding coupled with the minimal inter-communication between communities suggests possible ideological isolation.